Burnout Syndrome: a comparative-correlational study between teachers working at different education levels - de Moraes, Flávia Karolinny Santos; Vale, Joyce Karen Lima; Nunes, Hudson Fabrícius Peres; Drigo, Alexandre Jannota [UNESP]; de Souza Vale, Rodrigo Gomes; Borba-Pinheiro, Claudio Joaquim (Federacion Espanola de Asociaciones de Docentes de Educacion Fisica (FEADEF), 2023)
The study aimed to compare and correlate the signs of Burnout Syndrome (BS) in teachers who work at different levels of teaching in education, after the pandemic scenario. Teachers from the municipal, state and federal public education network at the levels of kindergarten, elementary, middle and higher education, working in the municipality of Tucuruí-PA, participated in the study. The study was characterized with a quantitative approach, of a descriptive nature with cross-sectional and correlational. Data collection used a self-administered assessment instrument divided into two blocks of questions: 1-Demographic data and 2-Maslach Burnout Inventory (MBI) which assessed Emotional Exhaustion (EE), Low Personal Fulfillment (LPF) and Depersonalization (D). After data collection, descriptive analysis and comparison of independent samples were performed. The results showed that there was a prevalence of medium risk for BS in the final score, precisely in elementary and higher education teachers. Depersonalization showed p<0.05 differences, where the superior and fundamental groups were more impacted compared to the Infantile and Medium groups. There was also a significant correlation p<0.05 between EE, BRP and D. Therefore, there is a preponderance of BS in education professionals from municipal, state and federal public institutions, which may indicate the presence of BS.
Síndrome de Burnout: un estudio comparativo-correlacional entre docentes que trabajan en distintos niveles educativos
Síndrome de Burnout: um estudo comparativo-correlacional entre docentes que atuam em diferentes níveis do ensino
Keywords: Burnout; Depersonalization; Psychological exhaustion; teachers